Vertical migration of cesium in weathered granite soil under flowing water condition depending on Cs concentration and states of dissolved organic matter. (15th March 2022) - Tatsuno, Takahiro; Hamamoto, Shoichiro; Nihei, Naoto; Nishimura, Taku
Abstract: After the accident at the Fukushima Daiichi nuclear power plant in Japan, the migration of radioactive cesium (Cs) in soils has become a crucial issue since this can negatively affect human health and the surrounding environment. Dissolved organic matter (DOM) may have different influences on Cs migration in soils depending on Cs adsorption sites with different selectivity. It is unclear how DOM affects the rapid migration of Cs in soils under flowing water conditions during rainfall events. This study evaluated the effects of DOM on Cs migration in weathered granite soil depending on Cs adsorption sites by conducting laboratory experiments under different DOM conditions and Cs concentrations in the liquid phase. Cs concentration can affect the fraction of Cs adsorbed onto differently selective sites, and DOM can have different influences on Cs migration in the soil accordingly. Under condition of high-Cs concentration, the DOM adsorbed on the soil reduced Cs migration due to increasing Cs electrostatic adsorption to less selective sites in the soil. Meanwhile, under low-Cs concentration, the DOM adsorbed on the soil enhanced Cs migration because the DOM on the soil decreased the Cs adsorption to highly selective sites. Furthermore, DOM in the liquid phase detached the Cs adsorbed on the less selective sites and enhanced Cs migration in the soil, regardless of the Cs concentration. Graphical abstract: Image 1 Highlights: Dissolved organic matter (DOM) might have different effects on Cs migration in the soil under flowing water condition depending on states of DOM and Cs concentration in the liquid phase. DOM adsorbed on the soil decreased Cs migration in the soil under high Cs concentration conditions because DOM might enhance Cs electrostatic adsorption to the less selective site, such as clay planar site. DOM on the soil increased Cs migration in the soil under low Cs concentration condition as DOM might depress Cs access to highly selective sites, such as Frayed edge site. DOM in the liquid phase might detach Cs electrically adsorbed on the soil solid phase, and increase Cs transport, regardless of Cs concentration in the liquid phase.